Lapachol Induces Clastogenic Effects in Rats - Maistro, Edson Luis [UNESP]; Fernandes, Diego Mota [UNESP]; Vieira Pereira, Fernanda Maria [UNESP]; Andrade, Sergio Faloni (Georg Thieme Verlag Kg, 2010)
Lapachol is a naturally occurring naphthoquinone derivative found in the heartwood of several plants, particularly those of the genus Tabebuia (Bignoneaceae). Despite its use as a therapeutic product with anti-inflammatory, analgesic, anti-psoriatic, trypanocidal effects, among others, its in vivo mutagenic potential has still not been investigated. This paper reports the effects after a single oral administration of lapachol in the in vivo micronucleus (MN) and chromosome aberration (CA) assays. Both assays were performed using bone marrow cells from male Wistar rats. The animals were treated by oral gavage with hydro-alcoholic solutions of lapachol at the doses of 122, 244 and 365 mg/kg, chosen on the basis of the LD(50) in male rats. The results show that the higher administered lapachol dose induced a significant increase in the frequency of micro-nucleated polychromatic erythrocytes (MNPCE) and CAs in rat bone marrow cells, indicating that lapachol shows clastogenic effects under the experimental conditions used.
Keywords: lapachol; micronucleus; naphthoquinone; chromosome aberrations; Tabebuia; Bignoneaceae